The Impact of Electricity Consumption to Human Development Index in Asian Countries: Analysis Panel Vector Error Correction Model - Suryanto, Suryanto; Gravitiani, Evi; Diswandi, Diswandi; Arintoko, Arintoko (International Journal of Energy Economics and Policy, 2023)
This study answers the question of the effect of the level of electricity consumption (LEC) on the level of human welfare both in the short and long term. Recently, many studies that investigated the impact of LEC to economic growth has been conducted. Most of them argued that electricity consumption have positive impact to economic growth. However, the study that analyzes LEC’s impact on the Human Development Index (HDI) and Happiness Index (HI) still needs to be completed. The research data uses secondary data sourced from the worldbank from 2012-2019. The number of countries as sample of this study were 38 countries in Asia. We choose and analyze the countries that have complete data for all variables until 2019. The analysis tool used is the Panel Vector Error Correction Model (PVECM). We analyzed data using PVECM because we wanted to understand the impact of LEC on HDI and HI both in the short and long run. The results revealed the relation between LEC and human welfare indicators. Finally, we found in the long run, there are no variables that have a significant effect on electricity consumption. Meanwhile, based on the short-term equation, it was found that in model 1 with the LEC dependent variable, it was found that only the previous period’s LEC variable was significant. In Model 2, with the HDI dependent variable, it is known that the previous period’s HDI variable has a significant effect. These results are also similar to the HI and LAK variables. The HI and LAK variables are only influenced by HI and LAK variables in the previous time lag. The implication of this study is increasing of electricity consumption would not direct impact on human development index and happiness index.